Prospects of Zakat as Tax Credit in a New Normal COVID-19 Period - Any Setianingrum; Nurul Huda; Perdana Wahyu Santosa (Center of Strategic Studies (PUSKAS) BAZNAS, 2021)
Previous research, regarding the prospect of zakat policy as a tax credit, was conducted using the Analytic Network Process (ANP) method, using expert respondents. To obtain findings from respondents with different backgrounds, to make it more comprehensive, this research was continued by using the SEM (Structural Equation Model) method, by filling in a questionnaire, as many as 235 respondents from all over Indonesia were random. The research objective is to determine the variables that affect the preferences and participation of muzaki and taxpayers, willing to pay taxes and zakat, increase public finances, which can be used as a solution to the sharp decline in aggregate economic supply and expenditure in Indonesia, due to the COVID-19 pandemic. The results showed that the regulatory variables, zakat incentives as tax credits, technology-based services, socialization and promotion have a significant effect on the preferences of muzaki and taxpayers. Meanwhile, regulatory variables, zakat incentives as tax credits, socialization and promotion have a significant effect on muzaki and taxpayer participation. Meanwhile, technology services and preferences in this study do not have a significant effect on the participation of muzaki and taxpayers. When all sectors of the commercial economy experience a decline or stagnate, the government must be able to move the philanthropic sector, so that the economy continues to run, aggregate demand and supply continues to run, and people's purchasing power is maintained, especially for low-income people.